Unveiling Constraints in Banana Value Chains: A Holistic Analysis in Palakkad District, Kerala - Nikhil, K S; Radhakrishnan, Aparna; Raghavan Sathyan, Archana; Thomas, Allan; Dileepkumar, R (Indian Journal of Extension Education, 2024)
Investigations into value chains, aiming to identify priority constraints experienced by value chain actors, play a vital role in comprehending socio-economic dynamics and formulating sustainable development strategies. The banana value chain in the Palakkad district of Kerala exhibits widespread distribution and significant fragmentation. Many stakeholders voiced their concerns, drawing attention to the challenges they faced in their daily operations. In this context a value chain-based study was conducted during October, 2022. Employing diverse research techniques such as interviews, focus group discussions, and the analytical hierarchy process (AHP), the study categorized constraints into economic, technical, social, and environmental groups. Results indicated that economic factors had the most substantial impact, followed by technical, social, and environmental constraints. The study highlights the profound influence of these constraints on the financial aspects of all involved stakeholders. It further emphasizes the necessity for targeted policy interventions and strategic planning to effectively address these issues and enhance the agricultural sector’s efficiency and economic viability in the area.
Keywords: Value chain; Actors; Financial loss; Policy interventions; Constraints; Solutions